Railway Development from the Aspect of Environmental Protection - Blašković Zavada, Jasna; Nikšić, Mladen; Kovačević, Dražen (Promet - Traffic&Transportation, 2002)
General development of civilisation and constant growth ofpopulation have inevitably resulted in an increased volume oftraffic and energy consumption. One of the consequences isalso the adverse effect on the environment, i.e. people, climateand nature. Compming individual forms of transport, it may benoted that railway, as mass carrier in passenger and freight trafficplays a significant role and has great responsibility. Sincerailway represents a very convenient form of transport regardingboth power and ecology, it has to provide significant contributionto the passenger and freight transport in the future, in a waywhich is friendlier to the environment than most other forms oftransport.This work analyses the cun-ent and future role of railway inthe transportation of people and goods. It mentions the mostimportant strategic orientations in the railway development,that would render it competitive and attractive compared toroad and air traffic. Special emphasis is put on economic efficiency,ecological sustainability and social justice. The possibilitiesof reducing energy consumption, i.e. C02 emissions, aswell as reducing hannful exhaust gases of Diesel railway tractionvehicles are given special consideration.